Fickle Commitment. Fostering political engagement in `the flighty world of online activism' - Julie Uldam (Copenhagen Business School (CBS), 2010)
In the wake of increasing disillusion with the potential of alternative online media for providing social movements with a virtual space for self-representation and visibility (Atton, 2002; Downing, 2001; Rodriguez, 2001) activists have been adopting online social media into their media practices. With their popular appeal and multimodal affordances social media such as YouTube and Facebook have reinvigorated hopes for the potential of the internet for providing social movements such as the Global Justice Movement, which is often misrepresented as a homogeneous and in a negative light in the mass media (Gamson and Wolfsfeld, 1993; Juris, 2008), with new possibilities for promoting self-representations to wider publics – beyond the echo chambers of alternative media (Cammaerts, 2007; Sunstein, 2001). In the mediation of institutional politics the increasing use of popular online spaces has brought about the term 'YouTube-ification of Politics' (Turnsek and Jankowski, 2008). However, two challenges remain: the first relates to fragmentation – the internet's properties as a `pull-medium' is argued to merely connect likeminded users (Cammaerts, 2007: 138). The second relates to 'lazy politics' – the internet's ephemeral properties are argued to facilitate brief participation in single-issue campaigns that fails to foster political engagement (Fenton, 2008a: 52). This thesis focuses on the latter. It addresses the possibilities of popular online spaces for fostering collective solidarity and political engagement in social movement organisations. It explores how these possibilities are played out in the online arena of popular sites employed by the two London-based social movement organisations: the World Development Movement (WDM) and War on Want. Drawing on the cases of WDM and War on Want, the thesis addresses three dimensions of these practices, exploring (1) rationales for using popular online spaces to promote the SMO agenda; (2) the social movement organisations' online campaigns; and (3) members' identifications with the campaigns through discourse analysis and interviews with SMO directors, campaign, outreach and web officers as well as SMO members. It is by analysing how SMOs use different online spaces as locations for strategic framing and the formation of political identities that we can begin to study how the internet may contribute to an agonistic public sphere where also voices of dissent are heard. The thesis is based on Mouffe's understanding of politics and the political as grounded in discourse but also based on a view of political engagement as conflictual, affective and sometimes irrational (Cammaerts, 2007; Fenton, 2009; Mouffe, 2005). Even though this does not mean that SMOs do not apply rational considerations in planning their strategic agendas for public visibility and legitimacy, it does mean that the study of these considerations need to take into account this dual character of political discourse as both rational and affective (Hajer and Versteeg, 2005). Therefore, we need to consider instrumental and affective issues to understand the relationship between strategic protest and the underlying dynamics of intragroup commitment (Griggs and Howarth, 2002; Snow et al., 1986) – the interconnections between strategy and identity, external resonance and internal commitment. In this way, the democratic potentialities of the internet can be seen as not only related to the ways in which SMOs communicate their agenda but also to potentialities for forging political identities and commitment (Fenton, 2008a).
hdl:10398/8211
Keywords: 650